Computational design and development of molecular imprint polymer for selective extraction of andrographolide from andrographis paniculata / \c Hemavathi Krishnan - Krishnan, Hemavathi (Faculty of Engineering Technology, 2018)
The scope of this research is to computationally design and develop molecular imprint polymer for selective extraction of andrographolide from A. paniculata plant extract. The study was conducted to selectively extract bioactive compound using simple and efficient technique. Therefore, molecular imprint technique was collaborated with solid phase micro extraction (SPME) and Quartz Crystal Microbalance (QCM) for the extraction and quantification of andrographolide from the A. paniculataplant extract.